2003
DOI: 10.1111/1467-7687.00282
|View full text |Cite
|
Sign up to set email alerts
|

The development of attentional orienting during the school‐age years

Abstract: This study was designed to assess the development of spatial attentional orienting during the school-age years. To that end, we used a cost-benefit attentional cueing task with short (100 ms) and long (800 ms) cue-to-target intervals to examine attentional processing independent of motor skills and perceptual processing in 200 7-17-year-olds and 40 adults. We found that orienting attention, disengaging attention and visual processing in an unattended location, were all progressively more accurate and faster wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 35 publications
6
43
0
Order By: Relevance
“…Rather, what seems to develop is the attention orienting itself, because RTs to congruent trials were always faster than RTs to both noncongruent and incongruent trials, at all ages. Therefore we suggest that what develops with age is a faster orienting of attention toward gaze-cued locations, in agreement with developmental studies using nongaze attention cueing paradigms (Schul et al, 2003;Wainwright & Bryson, 2002).Of specific interest to the present study was the extent to which different facial expressions modulate the GOE in a nonanxious population, and whether there were differences across the developmental trajectory. As reviewed in the introduction, larger GOEs have been reported for fearful faces in highly anxious participants (Fox et al, 2007;Mathews et al, 2003).…”
supporting
confidence: 88%
“…Rather, what seems to develop is the attention orienting itself, because RTs to congruent trials were always faster than RTs to both noncongruent and incongruent trials, at all ages. Therefore we suggest that what develops with age is a faster orienting of attention toward gaze-cued locations, in agreement with developmental studies using nongaze attention cueing paradigms (Schul et al, 2003;Wainwright & Bryson, 2002).Of specific interest to the present study was the extent to which different facial expressions modulate the GOE in a nonanxious population, and whether there were differences across the developmental trajectory. As reviewed in the introduction, larger GOEs have been reported for fearful faces in highly anxious participants (Fox et al, 2007;Mathews et al, 2003).…”
supporting
confidence: 88%
“…5 years old) need longer warning-to-target intervals in order to benefit from warning cues and are less able to sustain alertness over time compared to older children and adults Morrison, 1982). On the other hand, children show a progressive increase in orienting speed to valid orienting cues during childhood (Schul, Townsend, & Stiles, 2003). Several studies have shown that the ability to orient attention by means of peripheral as well as central cues seems to reach full maturation by age 10-11 years (Goldberg, Maurer, & Lewis, 2001;Waszak, Li, & Hommel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the ability to orient attention by means of peripheral as well as central cues seems to reach full maturation by age 10-11 years (Goldberg, Maurer, & Lewis, 2001;Waszak, Li, & Hommel, 2010). However, somewhat longer developmental courses have been observed when disengagement from an invalid location and reorienting to the valid one is needed, particularly under endogenous orienting conditions, as when long intervals between cue and target are utilized (Schul et al, 2003;Wainwright & Bryson, 2005). Finally, there is much evidence that young children experience more difficulty than older children and adults performing tasks that involve conflict.…”
Section: Introductionmentioning
confidence: 99%
“…The subject decides to orient attention toward a particular stimulus because of its importance according to the subject's goals, for example, looking for the sign indicating where the circus is. Even though some developmental studies have shown that children as young as 6 years of age are able to use expectations to endogenously orient their attention (Brodeur & Enns, 1997;Goldberg, Maurer, & Lewis, 2001;Schul, Townsend, & Stiles, 2003;Wainwright & Bryson, 2002, 2005, it is possible that endogenous orienting is not fully developed in these children. Indeed, endogenous orienting of attention may not be a unique construct, and the ability to orient attention in relation to expectations (i.e., toward expected stimuli) may be dissociated from the ability to endogenously inhibit the capture of attention by irrelevant stimuli (de Fockert, Rees, Frith, & Lavie, 2004;Michael, Garcia, Fernandez, Sellal, & Boucart, 2006).…”
mentioning
confidence: 99%